Increased Organohalogen Diversity after Disinfection of Water from a Prescribed Burned Watershed - UZUN, HABİBULLAH (AMER CHEMICAL SOC, 2021)
We evaluated impacts of prescribed burns on water quality by performing field sampling on adjacent first-order watersheds (Santee Experimental Forest, South Carolina), where one of the watersheds underwent a prescribed burn in 2016. We measured water quality parameters [dissolved organic carbon (DOC), nitrogen species, UV254 absorbance, and disinfection byproduct formation potential during chlorination and chloramination] before and after the burn. Using ultra-high-resolution mass spectrometry, we characterized dissolved organic matter features in raw water collected during the first postburn storm, as well as after chlorination and chloramination. After the burn, the median DOC to dissolved total nitrogen (DTN) ratio increased by 1.88 mg of DOC (mg of DTN)(-1) in the burned watershed. Likewise, the burned watershed showed a brief higher haloacetic acid yield after the burn [median of 95.6 mu g (mg of DOC)(-1)] compared to that of the unburned watershed. Despite similar molecular size distributions, more features were found (m/z 700-1000) for condensed aromatics and lignin-like features in the burned watershed. 'While chlorination yielded similar organohalogen diversity, chloramination yielded more halogenated molecular features in the burned watershed (m/z 300-600). The moderate impacts on DOC in this study suggest that prescribed fire likely poses a low risk to water quality.
Keywords: pyrogenic carbon; disinfection byproducts; ultra-high-resolution mass spectrometry; chemical fingerprint; dissolved organic matter; chloramination; fire; NDMA FORMATION POTENTIALS; DISSOLVED ORGANIC-MATTER; BY-PRODUCTS; WILDFIRE; CARBON; CHLORINE